2022
DOI: 10.3390/ijerph19148881
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Exerts Cytotoxic Effects in a Panel of Healthy Cell Lines and Strong Irritating Potential on Blood Vessels

Abstract: The use of tobacco products is a major global public health issue, as it is the leading cause of preventable death worldwide. In addition, nicotine (NIC) is a key component of electronic and conventional cigarettes. Although nicotine’s addictive potential is well known, its health effects are not entirely understood. Thus, the main objective of the present study was to evaluate its toxicological profile both in vitro, at the level of three healthy cell lines, and in ovo, at the level of the chorioallantoic mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 47 publications
(47 reference statements)
1
8
0
Order By: Relevance
“…According to a previous study, nicotine from conventional cigarettes induces a strong condensation of chromatin, fragmentation of nuclei and the appearance of apoptotic bodies in the nuclei of human keratinocytes. All these effects are more intense than those observed in the present case with nicotine derived from electronic cigarettes and chewing gum [9]. Moreover, Ruiz and colleagues examined the effects of nicotine on the nuclei of human mesenchymal stem cells, which are fibroblast-like cells found in several tissues, including the skin.…”
Section: Resultsmentioning
confidence: 63%
See 4 more Smart Citations
“…According to a previous study, nicotine from conventional cigarettes induces a strong condensation of chromatin, fragmentation of nuclei and the appearance of apoptotic bodies in the nuclei of human keratinocytes. All these effects are more intense than those observed in the present case with nicotine derived from electronic cigarettes and chewing gum [9]. Moreover, Ruiz and colleagues examined the effects of nicotine on the nuclei of human mesenchymal stem cells, which are fibroblast-like cells found in several tissues, including the skin.…”
Section: Resultsmentioning
confidence: 63%
“…Photographs were taken with the 20x objective, and the scale bar indicates 50 µm Electronic cigarettes have been controversially discussed in the past regarding their negative impact on the cardiovascular system [13]. The effects of nicotine on cardiomyocyte nuclei have been evaluated previously and it has been concluded that nicotine from conventional cigarettes is much more toxic at the cellular level than the nicotine studied in the present study [9]. The process of apoptosis is known to involve changes at the molecular and morphological levels.…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations